2014
DOI: 10.1111/brv.12131
|View full text |Cite
|
Sign up to set email alerts
|

The biology hidden inside residual within‐individual phenotypic variation

Abstract: Phenotypes vary hierarchically among taxa and populations, among genotypes within 2 populations, among individuals within genotypes, and also within individuals for repeatedly 3 expressed labile phenotypic traits. This hierarchy produces some fundamental challenges to 4 clearly defining biological phenomena and constructing a consistent explanatory framework. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
276
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(280 citation statements)
references
References 115 publications
3
276
0
1
Order By: Relevance
“…Individual variation in a trait represents the raw material for natural selection and the stability of differences between individuals impacts the efficiency of adaptive responses to selection (Roche et al, 2016). Between individual variation in a trait is generated by differential exposure to relatively stable environmental factors, such as mothering styles (see for instance Liu et al, 1997;Francis and Meaney, 1999;Caldji et al, 2000), or by heritable differences between individuals (Dingemanse et al, 2010b;Forsman, 2015;Westneat et al, 2015). Individual trait repeatability, defined as the proportion of phenotypic variance explained by consistent between individual differences, indicates whether a trait can evolve through selection in principle (Dingemanse and Dochtermann, 2013;Baugh et al, 2014): traits with high repeatability-that is high relative between individual variation-can potentially be selected for if between individual variation is generated by genetic differences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual variation in a trait represents the raw material for natural selection and the stability of differences between individuals impacts the efficiency of adaptive responses to selection (Roche et al, 2016). Between individual variation in a trait is generated by differential exposure to relatively stable environmental factors, such as mothering styles (see for instance Liu et al, 1997;Francis and Meaney, 1999;Caldji et al, 2000), or by heritable differences between individuals (Dingemanse et al, 2010b;Forsman, 2015;Westneat et al, 2015). Individual trait repeatability, defined as the proportion of phenotypic variance explained by consistent between individual differences, indicates whether a trait can evolve through selection in principle (Dingemanse and Dochtermann, 2013;Baugh et al, 2014): traits with high repeatability-that is high relative between individual variation-can potentially be selected for if between individual variation is generated by genetic differences.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction norm repeatability-that is how stable individuals are in their responses to environmental change over time-is expected only when individual attributes related to the costs and benefits of plasticity are stable over time. In the past years, research on average reaction norms and plasticity revealed that both can be subject to sexual and natural selection, and thus have important implications for environmental processes and trait evolution (Piersma and Drent, 2003;Nussey et al, 2005Nussey et al, , 2007Brommer, 2013;Dingemanse and Dochtermann, 2013;Westneat et al, 2015;Martin et al, 2017;Villegas-Ríos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Briffa et al [3] described six categories of behavioural variation but again arrived at residual variation within individuals as the finest level of behavioural organization. This fine scale residual variation [4] has also been described as consistency [5], stability [6,7] and recently as predictability and intraindividual variation (hereafter IIV) [3,[8][9][10][11]. Although such hierarchies represent a useful framework for discussing the structure of behavioural variation, the levels are not isolated from one another.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, hierarchical analysis of variance allow detection of patterns in the residual variance 560 that then provide new insights into behavioral strategies (Westneat et al 2015 Table 2. Effects of begging in previous visits on parental IVI and load mass.…”
mentioning
confidence: 99%